Get personalized answers to your unique questions on IDNLearn.com. Our platform offers detailed and accurate responses from experts, helping you navigate any topic with confidence.
Step-by-step explanation:
to "solve" this I need an equation.
this whole expression must be equal to something.
without that I can only try to simplify the expression.
remember that
a/b / c/d = ad / bc
so, here we have
3a/(((a²/x) - 1)(a/x - 1)) = 3a/(a³/x² - a²/x - a/x + 1) =
= 3a/(a³/x² - a²/x - a/x - a/a) =
= 3a/((a²/x² - a/x - 1/x - 1/a)×a) = 3/(a²/x² - a/x - 1/x - 1/a)